A Review of Synthetic and Earth's Resource-Based Slow-Release Fertilizers and Their Potential Role in Reducing Groundwater Pollution - Eki Naidania Dida; Solihin Solihin; Denny Kurniadie (Indonesian Institute of Sciences, 2022)
Groundwater is an essential water source for humans. Unfortunately, some groundwater resources have been contaminated by wastes from various sectors. Fertilizer also contributes to groundwater contamination. The nutrients from fertilizer that are not absorbed by the plant move towards groundwater reservoirs and contaminate the groundwater. Slow-release fertilizer is a solution to reduce groundwater pollution while maintaining fertilizer’s function as the sources of nutrients for plants. This paper discusses and reviews the relevant literatures related to groundwater, fertilizer, slow-release fertilizer, and earth’s based slow-release fertilizer. The release rate of nutrient elements from different types of fertilizer is also presented. The synthetic base slow-release fertilizers and earth’s resource-based slow-release fertilizers can hold nutrients longer than conventional chemical fertilizers when exposed to water. Two particular minerals that can be used as raw materials in slow-release fertilizer synthesis are analyzed using XRD. They are from hydrothermal silica and obsidian. The XRD analysis of hydrothermal silica and obsidian shows the presence of amorphous silica and other minerals. Silica in compacted slow-release fertilizer can control the release rate of nutrient elements from fertilizer.